Analysis of spatial experience - the example of the graden of Versailles - Szántó, Catherine (4D Journal of Landscape Architecture and Garden Art, 2011)
In current theoretical literature on land- scape architecture, the debate "space" versus "piacé" opposes two types of spatiality: the abstract homogeneous space of Science, and the meaningful space (piacé) of everyday life . The strongly geometrical garden types - such as the so-called French "classical" garden - are often accused of dismissing the experiential, place-making qualities of spatial design, and are opposed to more fluid geometries, such as that of the English "landscape" garden. This debate arises from a mistaken opposition between two modes of perceiving and manipulating space. Indeed, it is nőt their opposition, bút their association in a variety of combi- nations that allows fór the experiential richness and the unique spatial expe- rience offered by a specific place/space, such as, fór instance, the Gardens of Versailles.